Essentials of athletic injury management - Prentice, William E. PhD, ATC, PT, FNATA (New York, NY McGraw-Hill Education, 2020)
The eleventh edition of Essentials of athletic Injury Management provides the reader with the most current information on the subject of prevention and basic acre of sports injuries. The general philosophy of the text is that adverse effects of physical activity arising from participation in sport should be prevented to the greatest extent possible. However, the nature of participation in physical activity dictates that sooner or later injury may occur. In these situations, providing immediate and correct care can minimize the seriousness of an injury. Overall, this text is designed to take the beginning student from general to specific concepts. Each chapter focuses on promoting an understanding of the prevention and care of athletic injuries.
Fitness professionals, coaches, and the sports medicine team: defining roles -- Organizing and administering an athletic health care program -- Legal liability and insurance -- Preventing injuries through fitness training -- sports nutrition and supplements -- Selecting and using protective sports equipment -- Understanding the potential dangers of adverse environmental conditions -- Handling emergency situations and injury assessment -- Bloodborne pathogens, universal precautions, and wound care -- Wrapping and taping techniques -- Understanding the basics of injury rehabilitation -- Helping the injured athlete psychologically -- Recognizing different sport injuries -- The foot and toes -- The ankle and lower leg -- The knee and related structures -- The thigh, hip, groin, and pelvis -- The shoulder complex -- The elbow' forearm, wrist, and hand -- The spine -- The thorax and abdomen -- The head, face, ears, nose and throat -- General medical conditions and additional health concerns -- Substance abuse -- Preventing and managing injuries in young athletes
"This international student edition is for use outside of the U.S."--book cover
Includes bibliographical references and index
Keywords: Sports medicine; Sports injuries -- Prevention; Physical education and training